Measurement of degradation in li-po batteries using smartphone fast charging technologies - Gómez Solano, Juan Manuel (Universidad Escuela Colombiana de Ingeniería, 2025)
En este documento, el lector encontrará un problema que surge con las tecnologías de carga rápida para teléfonos móviles, específicamente la degradación de la batería. Para verificar esto, se realizó un experimento que requirió el diseño de un hardware que carga y descarga cíclica y controladamente dos baterías: una con carga rápida y otra con carga estándar. A lo largo de los ciclos de carga y descarga generados, se encontró un patrón de degradación que brinda al usuario información sobre el estado de la batería según el número de ciclos.

In this document, the reader will find a problem that arises with the fast charging technologies for cellphones, specifically the degradation on the battery. To verify this, an experiment was carried out that required the design of hardware that generated cyclical and controlled charging and discharging cycles. Throughout the charge and discharge cycles generated, a degradation pattern was found that gives the user information about the state of the battery and how long it could last over time according to the number of cycles.
Contents 1 Introduction 4 2 Objetives 5 3 State of art 6 3.1 Electrode damage 6 3.2 Temperature and charging levels 6 3.3 Cycles of charge 8 4 How does the cell phone battery charging process work? 9 4.1 CC/CV charging method/profile 9 4.1.1 Precharge Current Regulation Phase 9 4.1.2 Fastcharge Current Regulation Phase 9 4.1.3 Fastcharge Voltage Regulation Phase 9 4.2 Capacity 9 4.3 Constant charging current 10 4.4 Phone charging power chain 10 4.5 Linear chargers 10 4.6 Switched chargers 11 4.7 Charging protocols/specifications/standards 11 4.7.1 BC1.2 11 4.7.2 Special brands charging 12 4.8 Fast charging 12 4.8.1 Qualcomm Quick Charge (QC) and Samsung AFC 12 4.8.2 Power Delivery (PD) 12 4.9 Beyond. 13 5 Design 14 5.1 Basic design needs 14 5.2 Detailed design: Battery 15 5.3 Detailed design: Charging circuit 15 5.4 Detailed design: Discharge circuit 20 5.5 Detailed design: Peripherials 23 5.6 Detailed design: Microcontroller 24 5.7 PCB 26 5.8 Implementation and operation 29 5.9 Calibration 30 6 Results and analysis 31 6.1 Battery problems 31 6.1.1 Battery 1: HUAWEI P40 Lite 32 6.1.2 Battery 2: Motorola Moto G6 Play 34 6.1.3 Battery 3: Motorola Edge S30 36 6.1.4 Battery 4: GSP082752 38 6.2 Capacity comparison between standard and fast charging on the GSP082752 batteries . 40 6.3 Temperature comparison between standard and fast charging on the GSP082752 batteries 40 6.4 Temperature comparison between standard and fast charging on the other batteries 40 7 Conclusions 41 8 Acknowledgements 42
Keywords: Baterías para teléfonos celulares; Cell phones - Batteries; Baterías de almacenamiento; Storage batteries; Circuitos integrados; Integrated circuits; Corrientes eléctricas; Electric currents; batería; li-po; li-on; celular; teléfono; carga rápida; battery; cellphone; fast charging